Thin liquid film flow and heat transfer under spray impingement - Zhao, R. (2013)
A mathematical model was derived to investigate thin liquid film flow under spray impingement. Based on predicted flow patterns, a heat transfer model was developed to investigate the heat transfer performance in the non-boiling regime of spray cooling. The film thickness predicted by the thin film flow model favourably compares with reported experimental results obtained at different measurement locations and nozzle inlet pressures. It is found that the film thickness is sensitive to droplet flux distribution but not the nozzle inlet pressure. The comparison of the heated surface temperature between the proposed heat transfer model and the published experimental data shows good agreement.